The Effects of Riluzole on Cisplatin-induced Ototoxicity - Bezgin,Selin Üstün (2019)
Abstract Introduction Riluzole (2-amino-6-trifluoromethoxy benzothiazole) is known as a neuroprotective, antioxidant, antiapoptotic agent. It may have beneficial effects on neuronal cell death due to cisplatin-induced ototoxicity. Objective To evaluate the effect of riluzole on cisplatin-induced ototoxicity in guinea pigs. Methods Twenty-four guinea pigs, studied in three groups, underwent auditory brainstem response evaluation using click and 8 kHz tone burst stimuli. Subsequently, 5 mg/kg of cisplatin were administered to all animals for 3 days intraperitoneally (i.p.) to induce ototoxicity. Half an hour prior to cisplatin, groups 1, 2 and 3 received 2 ml of saline i.p., 6 mg/kg of riluzole hydrochloride i.p., and 8 mg/kg of riluzole hydrochloride i.p., respectively, for 3 days. The auditory brainstem responses were repeated 24 hours after the last drug administration. The cochleae were analyzed by transmission electron microscopy (TEM). Results After drug administiration, for 8,000 Hz stimulus, group 1 had significantly higher threshold shifts when compared with groups 2 (p < 0.05) and 3 (p < 0.05), and there was no significant difference in threshold shifts between groups 2 and 3 (p > 0.05). Transmission electron microscopy findings demonstrated the protective effect of riluzole on the hair cells and the stria vascularis, especially in the group treated with 8 mg/kg of riluzole hydrochloride. Conclusion We can say that riluzolemay have a protective effect on cisplatin- induced ototoxicity. However, additional studies are needed to confirm these results and the mechanisms of action of riluzole.